Rivers need floods: Management lessons learnt from the regulation of the Norwegian salmon river, Suldalslågen. (14th October 2019) - Saltveit, Svein Jakob; Brabrand, Åge; Brittain, John E.
Abstract: The Norwegian river Suldalslågen, known for its population of large‐sized Atlantic salmon ( Salmo salar ), has been regulated for hydropower in 1966–1967 and in 1980. The initial regulation increased winter flows and reduced summer flows and major floods. The second regulation, involving abstraction of water to a power station in an adjacent fjord, led to a strong reduction in flow. In addition to implementing different flow regimes, many remedial actions have been taken, often concurrently, making it almost impossible to detect the effect of single measures. In addition, the monitoring data have not always been consistent as regards methods and scope, and also, few data are available for preregulation conditions. This highlights major challenges in the long‐term management of regulated rivers. The absence of major floods after regulation led to increased sedimentation and encouraged carpet mosses. This reduced interstitial spaces, creating a poor habitat for salmon fry and benthic invertebrates. The knowledge gained from the wide‐ranging studies of the different flow regimes have enabled the environmental authorities to devise a final regulation regime from 2012. The final flow regime focused on biological values and functions to sustain the strain of wild, large adult salmon. The catch of wild salmon >7 kg has in fact increased since 2010 and stabilized between 1 and 2 metric tons, although the yield of large salmon prior to 1994 is unknown. In addition, the increase in the catch of large salmon is based on hatchery fish. Hatchery fish have also to a large extent contributed to the increase in the total salmon catch in recent years. Thus, that the catches in Suldalslågen are now at an all‐time high is not due to improved conditions in the river but likely to hatchery fish.